PRESERVATION OF MALAY STUDY: SELECTED CASE STUDY VIA GOOGLE SCHOLAR: PEMELIHARAAN PENGAJIAN MELAYU: KAJIAN KES TERPILIH MELALUI GOOGLE SCHOLAR - Husain, Haslina; Tamjehi, Haslan (Jurnal Pengajian Melayu (JOMAS), 2024)
In the university library, various materials are readily available, encompassing various formats such as books, journals, media collections, and online databases. Among higher education students, there is a not able preference for social science books, particularly those focused on Malay Studies, serving as valuable references for assignments and theses. Online databases like Project Muse are also frequently consulted to supplement academic work. The primary goal of this study is to analyze the availability of articles related to our title, "Preservation of the Malay Studies Case Study," through an exploration conducted on Google Scholar. Notably, Google Scholar emerges as an open-source platform preserving a collection of Malay Studies articles, benefiting a wide audience. The selection and review of around ten case studies are crucial, considering criteria such as the case study title, material type, and citation count. Two case studies have garnered over a hundred citations, while six have exceeded 20. The distribution includes eight journal articles, one book, and an article in proceedings. These case studies predominantly delve into preserving historical culture within the context of Malay studies, encompassing research conducted in Malaysia, Indonesia, and Singapore. Acknowledging limitations, the chosen search keywords, "preservation" AND "Malay study," provide direction for future researchers to tailor their searches based on specific research areas.